EFEKTIVITAS RUBRIK MULTILITERASI DALAM MENGUKUR KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Maya Eka Purwanti; Intan Sari Rufiana; Sri Rahayuningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the limited effectiveness of conventional assessment practices in measuring elementary students’ critical thinking skills, particularly in the context of 21st-century learning demands. The research aims to analyze the effectiveness of multiliteracy-based rubrics in assessing and improving students’ critical thinking skills, including interpretation, analysis, evaluation, and inference. This study employed a quantitative approach with a quasi-experimental design using a one-group pretest-posttest model. The sample consisted of elementary school students selected through purposive sampling. Data were collected through critical thinking tests and analyzed using the N-Gain formula to determine the level of improvement. The results indicated a significant increase across all indicators: interpretation (N-Gain = 0.7), analysis (0.716), evaluation (0.695), and inference (1.455). These findings demonstrate that multiliteracy rubrics are effective not only as assessment tools but also as instruments to enhance higher-order thinking skills. However, the unusually high N-Gain in inference suggests the need for further validation of scoring procedures. Overall, the integration of multiliteracy rubrics contributes positively to structured, authentic, and meaningful assessment practices in elementary education.